2007
DOI: 10.1097/01.mca.0000236292.86930.e3
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasound-based comparative study on carotid plaques in HIV-positive patients vs. atherosclerotic and arteritis patients: atherosclerotic or inflammatory lesions?

Abstract: Our study evidenced that the ultrasonographic structure of the epi-aortic lesions in HIV-positive patients substantially differ from those of the plaques in atherosclerotic patients, although they share similar characteristics with patients affected by arteritis. Further investigations are warranted to better define the structure and the mechanism of onset of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 16 publications
1
35
1
2
Order By: Relevance
“…Maggi et al evaluating patients with HIV and advocate the hypothesis that CMI is thickened more in the HIV group, which use the IP protocol is the cause of the thickening and that the lesions found in these patients are similar to arteritis and substantially different from atherosclerotic plaques [66], [69], [71], [72]. The present study does not confirm this hypothesis of thickening CMI in patients with HIV.…”
Section: Hiv Infection May Affect the Natural History Of Atherogenesiscontrasting
confidence: 56%
See 1 more Smart Citation
“…Maggi et al evaluating patients with HIV and advocate the hypothesis that CMI is thickened more in the HIV group, which use the IP protocol is the cause of the thickening and that the lesions found in these patients are similar to arteritis and substantially different from atherosclerotic plaques [66], [69], [71], [72]. The present study does not confirm this hypothesis of thickening CMI in patients with HIV.…”
Section: Hiv Infection May Affect the Natural History Of Atherogenesiscontrasting
confidence: 56%
“…The study using IMT has been performed in patients with acquired immunodeficiency syndrome (AIDS) in the investigation of risk factors for atherosclerosis as an early marker, but there are few studies prospectivos [71], [72].…”
Section: Hiv Infection May Affect the Natural History Of Atherogenesismentioning
confidence: 99%
“…Some authors suggested that the pathogenetic mechanism responsible for carotid lesions associated with HIV infection may be more similar to an inflammatory process than to the classical atherogenesis [204,205]. Some retrospective and prospective studies have shown that the incidence of myocardial infarction in HIV-positive subjects treated with ART tends to be higher than in the general population, particularly in those receiving a PI-based treatment [206].…”
Section: Insulinmentioning
confidence: 99%
“…In order to better evaluate the characteristics of the plaques that showed improvements with respect to those that remained unmodified, we applied a method already described in other issues to distinguish inflammatory from atheromasic patterns (17,18). In brief, the following ultrasound color-Doppler characteristics were examined: echogenicity of the lesion with respect to the vessel wall; presence of acoustic shadows inside the lesion; homogeneity of the lesion wall; profile of the endoluminal surface; and the presence or absence of a cleavage plain.…”
Section: Methodsmentioning
confidence: 99%